Balanço hídrico dinâmico em solo sem vegetação - de A Carvalho, Sérgio Marcos; Chohaku Sediyama, Gilberto; Bernardo, Salassier; Ferreira, Paulo Afonso (Revista Ceres, 2025)
This study involved a soil moisture model simulating soil moisture value under natural weather conditions. The predicted values were tested against measured values for 48 consecutive days (May 02 thru June 19, 1986) in the physical control volume.